Safety assessment of the process Lietpak, based on the EREMA MPR technology, used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Lietpak (EU register number RECYC327), which uses the EREMA MPR technology. The input material is hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, including no more than 5% PET from non‐food consumer applications. The flakes are heated in a ■■■■■ reactor under vacuum. Having examined the challenge test provided, the Panel concluded that the ■■■■■ decontamination (step 2), for which a challenge test was provided, is critical in determining the decontamination efficiency of the process. The operating parameters to control the performance of this step are temperature, pressure and residence time. It was demonstrated that this recycling process is able to ensure a level of migration of potential unknown contaminants into food below the conservatively modelled migration of 0.1 μg/kg food, derived from the exposure scenario for infants, when such recycled PET is used at up to 100%. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, including drinking water, for long‐term storage at room temperature or below, with or without hotfill. Articles made of this recycled PET are not intended to be used in microwave or conventional ovens and such uses are not covered by this evaluation.